2019
DOI: 10.1002/dc.24251
|View full text |Cite
|
Sign up to set email alerts
|

Are cytologic and histopathologic features of hot thyroid nodules different from cold thyroid nodules?

Abstract: Background We aimed to compare the cytology and histopathology results of hot, cold, and warm nodules in patients who had thyroidectomy due to toxic multinodular goiter (TMNG). Methods Five hundred and nine thyroid nodules from 413 patients who had operation with TMNG were included in this retrospective study. The nodules were categorized as hot, cold, and warm groups. The cytology and histopathology results were compared. Results The 509 thyroid nodules were grouped as hot (n = 364 [71.5%]), cold (n = 122 [24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
3
6
0
2
Order By: Relevance
“…Our finding of a considerable frequency of malignancy in suspicious or indeterminate autonomous nodules on US agrees with some studies 10,11,14 . However, a recent study found no malignancy in any of 17 Kwak‐TIRADS 4B nodules or 5 Kwak‐TIRADS 4C nodules 5 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding of a considerable frequency of malignancy in suspicious or indeterminate autonomous nodules on US agrees with some studies 10,11,14 . However, a recent study found no malignancy in any of 17 Kwak‐TIRADS 4B nodules or 5 Kwak‐TIRADS 4C nodules 5 .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, malignancy was not documented in any of the 28 nodules whose cytology was benign. The high‐negative predictive value of benign cytology in autonomous nodules has also been reported in other studies, 11,13,14,20,21 as well as the high probability of confirmation of malignancy in malignant/suspicion for malignancy cytology 11,12,14 …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Dies stellt somit auch den Stellenwert einer möglichen Feinnadelaspirationszytologie infrage. Zwar zeigen zytologische Untersuchungen heißer Knoten in 3,8 % Malignität [ 1 ], wobei jedoch die Aussagefähigkeit bei follikulären Neoplasien bekanntermaßen äußerst limitiert ist. Daher scheint eine zytolgische Untersuchung heißer Knoten selbst bei dem Verdacht auf ein Malignom entbehrlich.…”
Section: Diskussionunclassified
“…In einigen Publikationen werden z. T. allerdings deutlich höhere Malignom-Quoten bei "heißen" Knoten berichtet, als dies hierzulande im Bewusstsein ist. In einer relativ aktuellen türkischen Studie mit 509 Knoten (71,5 % "heiß" vs. 24,0 % "kalt" vs. 4,5 % "warm") bei 413 Patienten, welche sich einer Schilddrüsen-OP wegen funktioneller Autonomie unterzogen, fanden sich Malignitätsraten von 3,8 % vs. 6,6 % vs. 4,3 %, ohne dass die Unterschiede zwischen den Gruppen statistisch signifikant waren [19].…”
Section: Introductionunclassified